Rus and nomads in X – the ﬁrst third of the XII centuries: from military confrontation to allied relations - O. A. Kleymenova (Nomadic Civilization: Historical Research)
The article is devoted to the analysis of relations between the population of Ancient Rus and nomads (Pechenegs, Torks, Polovzy) in the Xth – ﬁrst third of the XIIth centuries. The relevance of this topic is due to the fact that for a long time in in historiography the attitude towards the history of nomadic societies, which were classiﬁed as non-historical, prevailed. Hence, the multilateral nature of contacts between sedentary and steppe peoples often was reduced to a description of the predominantly military aspect of these relations. In pre-revolutionary works, it was traditional to contrast the nomads, as barbaric, uncivilized peoples, with the agricultural population, who, according to some researchers, had a higher level of development and culture. At the present stage, historians, archaeologists, ethnologists, etc. are engaged in the study of nomads, an interdisciplinary approach is postulated. The article emphasizes that contacts between the nomadic and sedentary population of Ancient Rus were not limited to military confrontation, but were completed by peaceful forms of cooperation and interaction, which affected both the historical development of nomadic peoples and the formation of Old Russian State. The rivalry for political supremacy in Ancient Rus largely determined the originality of contacts between nomadic and agricultural peoples. Military alliances were supported by peace treaties, accompanied by the conclusion of marriage alliances, which later becomes a frequent event. The contact persons were practically all social strata (the highest aristocracy, the military, merchants, religious missionaries). More active interaction was observed in those regions where nomads and farmers lived mixed.